2020
DOI: 10.31933/jimt.v2i1.314
|View full text |Cite
|
Sign up to set email alerts
|

Peran Product Knowledge Terhadap Persepsi Risiko Minuman Kekinian

Abstract: Penelitian ini tentang peran product knowledge terhadap persepsi risiko psikologi, persepsi risiko fisik dan pengaruhnya terhadap repurchase intention. Desain penelitian ini menggunakan penelitian eksploratif, deskriptif dan kuantitatif. Penentuan sampel penelitian menggunakan Mahasiswa/i Universitas Mercubuana yang pernah mengkonsumsi minuman kekinian dengan teknik purposive sampling yang akan disebar kepada minimal 180 Mahasiswa/i. Temuan ini membuktikan product knowledge memiliki pengaruh positif terhadap p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…As is the case (Kamalul Ariffin et al, 2018) that persepei perceived risk has a significant negative influence on the intention of online purchases. Then research by (Pudaruth & Nursing, 2017;Wingate, 2019;Hamdan & Raharja, 2020) also found the risk of negative and significant effect on the purchase intention.…”
Section: Hypothesis Testingmentioning
confidence: 92%
“…As is the case (Kamalul Ariffin et al, 2018) that persepei perceived risk has a significant negative influence on the intention of online purchases. Then research by (Pudaruth & Nursing, 2017;Wingate, 2019;Hamdan & Raharja, 2020) also found the risk of negative and significant effect on the purchase intention.…”
Section: Hypothesis Testingmentioning
confidence: 92%
“…Product quality, nilai produk, kenyamanan transaksi, dan cara komunikasi dengan pelanggan adalah beberapa faktor yang mempengaruhi customer satisfaction. Customer satisfaction dianggap mempunyai kaitan yang erat dengan repurchase intention (Hamdan & Raharja, 2020). Dengan adanya customer satisfaction maka tingkat repurchase intention pelanggan juga akan meningkat.…”
Section: Abstrakunclassified
“…However, it is not easy to build consumer confidence in order to intend to use healthcare applications. The importance of conducting a study on intentions has been carried out by previous research (Endro & Achmad, 2015;Hamdan et al, 2020;Idris & Kasmo, 2017;Imaningsih, 2019;Riskhi et al, 2018), and many other researchers. While the factors that influence intention such as perceived benefits (Lim et al, 2016;Tanadi et al, 2015), perceived convenience (Athapaththu & Kulathunga, 2018;Rekarti & Hertina, 2014;Silva et al, 2019), and various other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has examined many factors that influence behavioral intentions such as social influence (Hoque & Sorwar, 2017;Quaosar et al, 2018), health awareness, (To et al, 2019), issues of trust (Astini, 2020), perceived benefits (Rekarti & Hertina, 2014), perceived ease and use (Wu & Chen, 2017), perceptions of risk and trust (Mosunmola et al, 2019), trust (Bhandari & Rodgers, 2018), and many other factors. In addition, previous research has examined important factors and become the main consideration of consumers regarding the intention to use mHealth application, namely: perceived ease and use and the content of the website (Athapaththu & Kulathunga, 2018), the experience of using (Anderson et al, 2016), trust, perceived risk, perceived ease and use (Bartelt & Moqbel, 2016), risk perception (Hamdan et al, 2020;Sang & Cheng, 2020), perceived usefulness, perceived ease of use (Ali Saare et al, 2019;Alloghani et al, 2015), perceived risk and negative e-WOM (Wakhida & Sanaji, 2020), perceived ease and use, attitudes (Hussein et al, 2017;Shemesh & Barnoy, 2020;Tasmil, 2014), false reviews and risk perception (Wingate, 2019).…”
Section: Introductionmentioning
confidence: 99%